2013
DOI: 10.5267/j.msl.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement using balanced scorecard: A case study of pipe industry

Abstract: Strategic assessment of the organizational performance in the industrial environment is one of the primary and essential prerequisites for developing improvement plans in organizations. This issue is so crucial that one of the on-going affairs in the organizations is to identify the weakness and strength points. One of the effective models for assessing the organizations performance is balance scorecard (BSC) model, which examines all the aspects of an organization. The proposed study of this paper investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…The study mentions how Kaplan and Norton devised a tool, the BSC, "to connect performance measures and perspectives of the business strategic vision; financial, customer, internal processes and learning and growth." The same notion is emphasised in the research by Danaeia and Hosseinib (2013). Business in the 21st century is focused on ensuring firms in addition to making profits also make effort to care for their consumers and the environment.…”
Section: Betamentioning
confidence: 96%
See 1 more Smart Citation
“…The study mentions how Kaplan and Norton devised a tool, the BSC, "to connect performance measures and perspectives of the business strategic vision; financial, customer, internal processes and learning and growth." The same notion is emphasised in the research by Danaeia and Hosseinib (2013). Business in the 21st century is focused on ensuring firms in addition to making profits also make effort to care for their consumers and the environment.…”
Section: Betamentioning
confidence: 96%
“…As emphasised by Danaeia, and Hosseinib, (2013), the most widely used tool for measuring performance is the balance scorecard (BSC) because of its capabilities of utilising both financial and non financial information to evaluate organisational performance effectively and more complete. The balance scorecard compliments financial data with internal processes, operational measure of customer satisfaction, improvement and innovation activities.…”
Section: Manufacturing Performancementioning
confidence: 99%
“…Mozaffari et al (2012) performed a BSC method to measure the performance of a university based organization based on an adaptation of fuzzy numbers for handling the existing uncertainty on the numbers. Danaei and Hosseini (2013) investigated the existing strategic objectives in the strategy map of a pipe company located in city of Shiraz, Iran and designed a questionnaire and distributed it among 31 managers, 94 regular employees and 110 customers of this firm for the fiscal year ended 2011. The results of their study indicated that the firm could reach 41.4% of its financial objectives, 87.38% of its customers' requirements, 66.13% of internal processes and 70.94% of its learning necessities according to four major BSC requirements.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that learning and development was number one priority with relative importance of 0.491, followed by customer with relative importance of 0.293, internal process with relative importance of 0.173 and financial affairs comes at last with relative weight of 0.043. Danaei and Hosseini (2013) studied the existing strategic objectives in the strategy map of a pipe company located in city of Shiraz, Iran and reported that the firm could reach 41.4% of its financial objectives, 87.38% of its customers' requirements, 66.13% of internal processes and 70.94% of its learning necessities according to four major BSC requirements. Nemati et al (2013) presented a technique to learn the effect of knowledge management (KM) practices on organizational performance.…”
Section: Introductionmentioning
confidence: 99%